WAYS OF ADDRESSING, EXPRESSING POLITENESS (TAMADDUN NURI JURNALI, 2024)
This article discusses the time of speaking in English, the advantages and efficacy of communication, and the various contexts in which it can be used. There are suggestions for language room décor and vocabulary to employ in English conversations with partners. We could delve into the benefits of effective communication in English, such as improved relationships, clearer understanding of ideas, successful negotiation, and enhanced career prospects.